45. THE CURRENT STATUS OF THE USE OF PRENATAL, PERINATAL, AND POSTNATAL CARE SERVICES BY ETHNIC MINORITY WOMEN IN DINH HOA DISTRICT, THAI NGUYEN IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of antenatal, intrapartum, and postpartum care services utilization among ethnic minority women in Dinh Hoa, Thai Nguyen in 2024.Methods: This study used a cross-sectional design, interviewing 307 ethnic minority women in Dinh Hoa, Thai Nguyen through a structured questionnaire, developed based on the research objectives and adapted from the UNFPA questionnaire.Results: Regarding antenatal care, 100% of women had at least one antenatal check-up, and 93.8% had at least four check-ups; 97.4% used services within the first 16 weeks of pregnancy. A total of 98.0% received care at public health facilities, and 98.7% were examined by healthcare staff. For intrapartum care, 99.3% of women gave birth at health facilities, all with the support of skilled healthcare personnel. Concerning postpartum care, 97.1% received services from healthcare staff, and 59.6% were examined at district-level or higher hospitals. The rate of infant care within the first 48 hours after birth was 97.7%. A total of 34.2% underwent newborn screening, and 95.4% received postpartum care at home within the first six weeks after birth.Conclusion: The utilization of antenatal, intrapartum, and postpartum care services was high. Electronic health interventions effectively improved maternal and child healthcare service utilization. Expanding electronic health interventions for ethnic minority women is essential.
Keywords: Antenatal care; intrapartum care,; postpartum care; ethnic minorities